2006
DOI: 10.1111/j.1467-9604.2006.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the special needs assistant supporting pupils with special educational needs in Irish mainstream primary schools

Abstract: In this article the author describes a small-scale study into the role of the special needs assistant (SNA) s u p p o rting the inclusion of pupils with learning difficulties in the Irish Republic. The findings regarding the perspectives of teachers, principals, SNAs, pupils supported by SNAs and their parents on the support offered to three pupils are also described. The actual (as distinct from the prescribed) role of SNAs, including the issue of SNAs working in a general rather than a pupil-specific capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 10 publications
0
32
0
4
Order By: Relevance
“…Although TAs reported that they worked with all students (Angelides et al, 2009;Howard & Ford, 2007;Liston et al, 2009;Logan, 2006), and educated classmates about how to be supportive of peers with disabilities (Dolva et al, 2011), Webster & Blatchford (2013 observed TAs interactions in inclusive classrooms and found that TAs rarely worked with students without disabilities.…”
Section: Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TAs reported that they worked with all students (Angelides et al, 2009;Howard & Ford, 2007;Liston et al, 2009;Logan, 2006), and educated classmates about how to be supportive of peers with disabilities (Dolva et al, 2011), Webster & Blatchford (2013 observed TAs interactions in inclusive classrooms and found that TAs rarely worked with students without disabilities.…”
Section: Research Questionmentioning
confidence: 99%
“…Several studies found that TAs performed roles that fostered student learning, teaching, and inclusion. Based on interviews and/or surveys, teachers noted that the availability of TAs had a beneficial impact on student learning (Haycock & Smith, 2011), job satisfaction, stress levels, and workloads ; and teachers, students, parents, and administrators reported that TAs positively supported their school's inclusion of students with disabilities (Logan, 2006). Angelides et al (2009) and Webster et al (2010) observed that TAs performed roles that fostered the learning and socialization of students with disabilities including increased participation and engagement in instructional activities, decreased student off-task behaviour and disruptions, and greater socialization with peers.…”
Section: Research Questionmentioning
confidence: 99%
“…In England and Ireland the use of additional classroom support has been seen as an important factor in the promotion of inclusive schooling (Roaf 2003;Logan 2006;O'Neill & Rose 2007). A significant increase in the numbers of adults playing supportive roles in schools has led to a range of different models of support, few of which have been subjected to critical scrutiny.…”
Section: Introductionmentioning
confidence: 99%
“…In many countries the role of non teaching staff working in classrooms has been focused on direct provision for pupils with SEN. Often, as is the case in the UK this includes involvement in pedagogical activity with pupils under the supervision of a teacher (Groom 2006). In Ireland the role of the special needs assistant has been shaped in a distinct manner which is focused upon the care needs of pupils and is in many respects divorced from curriculum intervention or support for teaching (Carrig 2004;Logan 2006). However, parallels can be drawn here with other roles designated to promote inclusion within the Irish education system, such as that of the resource teacher.…”
Section: As Discussion Around the Influence Of Teacher Training On Imentioning
confidence: 99%